Sputtering target and sputtering target assembled product
By adjusting the atomic ratio of Fe and Pt and adding other elements to form an alloy with high oxide content, the crack problem caused by alloy brittleness during the HDD magnetic recording layer manufacturing process is solved, and the yield strength of the propelling target and the quality of the HDD magnetic recording layer are improved.
Patent Information
- Application Number
- JP2023159119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-22
AI Technical Summary
When manufacturing the magnetic recording layer of HDD, when using magnetic alloys such as Fe-Pt system as the propelling target, the sintered body structure of the prepared oxides dispersed in the base metal is brittle, resulting in the problem of cracks and cracks easily during the manufacturing process.
By adjusting the atomic ratio of Fe and Pt between 34 and 55, ensure that the total concentration of Fe and Pt reaches 50 mol% or more, and add 0.5 to 15 mol% of other elements, such as Ag, Au, B, etc. to the alloy to form an oxide phase of 40 vol% or more, and the average oxidation particle size is controlled to be 4.0 μm or less to improve the yield strength of the alloy.
The cracks and crack problems of the alloy during the manufacturing process are effectively suppressed, the yield strength of the projectile target is improved, and the quality of the HDD magnetic recording layer is ensured.
Smart Images

Figure 2025050365000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a sputtering target and a sputtering target assembly, and primarily to a sputtering target for the production of films for HDDs. [Background technology]
[0002] The layers constituting hard disk drives (HDDs) that employ perpendicular magnetic recording are made of materials based on ferromagnetic metals such as Co, Fe, and Ni, and the recording layers are often made of composite materials consisting of ferromagnetic alloys such as Co-Cr, Co-Pt, Co-Cr-Pt, and Fe-Pt, which are mainly composed of Co and Fe, and non-magnetic inorganic materials. Thin films for magnetic recording media such as hard disk drives are often produced by sputtering sputtering targets containing the above materials, due to their high productivity.
[0003] In general, sputtering targets are manufactured by first crushing and mixing raw material powders, and then hot pressing the resulting mixture to obtain a sintered body. After this, HIP (Hot Isostatic Pressing) processing may be performed to increase the density of the sintered body. The sintered body thus obtained is processed on a lathe to manufacture a target of a specified shape (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6030271 [Patent Document 2] Patent No. 6305881 Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, a composite material consisting of a ferromagnetic alloy such as an Fe-Pt alloy and a nonmagnetic inorganic material is useful as a recording layer for a HDD. However, when a sintered body having a structure in which oxides are dispersed in a base metal containing Fe and Pt is manufactured as a sputtering target for producing such a recording layer, the sintered body having this composition is relatively brittle, and there is a problem that cracks and breakage occur during the manufacturing process.
[0006] Therefore, an object of an embodiment of the present invention is to provide a sputtering target and a sputtering target assembly that can effectively suppress the occurrence of cracks and breakage during the manufacturing process. [Means for solving the problem]
[0007] The above problems are solved by the present invention, which is specified as follows. 1. A composition comprising: (1) Fe; (2) Pt; (3) one or more elements selected from Ag, Au, B, Co, Cr, Cu, Ga, Ge, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Si, Sn, Ta, W, V, and Zn; and (4) the balance; The atomic ratio of the (1) Fe to the (2) Pt is 34 to 55 at %, The total concentration of the (1) Fe and the (2) Pt is 50 mol % or more, The content of the element (3) is 0.5 to 15 mol% in total, The remainder of the (4) is an oxide, which may selectively contain impurities, and the volume fraction of the oxide is 40 vol.% or more; The average grain size of the oxide phase was calculated using ImageJ with a magnification of 3000x. 2 The sputtering target is as follows: 2. The sputtering target according to 1 above, having a bending strength of 300 MPa or more. 3. The sputtering target according to 1 or 2 above, wherein the oxide contains an oxide of Si. 4. The sputtering target according to 3, wherein the oxide further contains one or more oxides of elements selected from Al, B, Ba, Be, Ca, Ce, Cr, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr. 5. A sputtering target according to any one of 1 to 4 above, A backing plate bonded to the sputtering target; A sputtering target assembly comprising: Effect of the Invention
[0008] According to the embodiments of the present invention, it is possible to provide a sputtering target and a sputtering target assembly that can effectively suppress the occurrence of cracks and breakage during the manufacturing process. [Brief description of the drawings]
[0009] [Figure 1] This shows an example of a binarized image and the original image in image analysis using ImageJ. [Diagram 2] This is a screenshot of the settings for binarization processing using ImageJ. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Next, the embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the present invention is not limited to the following embodiments, and that appropriate changes and improvements in the design may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.
[0011] <Sputtering target> The shape of the sputtering target according to the embodiment of the present invention is not particularly limited, and may be a flat plate (including a disk or rectangular plate), a cylindrical shape, or any other shape.
[0012] The sputtering target according to the embodiment of the present invention comprises (1) Fe, (2) Pt, (3) one or more elements selected from Ag, Au, B, Co, Cr, Cu, Ga, Ge, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Si, Sn, Ta, W, V, and Zn, and (4) the balance. The balance of (4) is an oxide and may selectively contain impurities. The sputtering target according to the embodiment of the present invention has a metal phase containing ferromagnetic materials Fe and Pt, and a phase containing an oxide other than the metal phase, and can be given the function of a magnetic thin film.
[0013] In the sputtering target according to the embodiment of the present invention, the atomic ratio of Fe to Pt is 34 to 55 at %. That is, the atomic ratio of Fe to Pt in the sputtering target is as follows: 100-X Pt X In the above, X satisfies 34≦X≦55. When the Fe and Pt in the sputtering target satisfy such an atomic ratio, the function as a magnetic thin film is improved. The atomic ratio of Fe and Pt is preferably 40≦X≦53, and more preferably 44≦X≦51.
[0014] The sputtering target according to the embodiment of the present invention has a total concentration of Fe and Pt of 50 mol% or more. When the total concentration of Fe and Pt in the sputtering target is 50 mol% or more, the magnetic properties are improved. The upper limit of the total concentration of Fe and Pt is not particularly limited, but is preferably 80 mol% or less from the viewpoint of ensuring grain boundary material. Moreover, the total concentration of Fe and Pt is more preferably 50 to 75 mol%, and even more preferably 50 to 70 mol%.
[0015] The sputtering target according to the embodiment of the present invention has a total content of at least one element selected from Ag, Au, B, Co, Cr, Cu, Ga, Ge, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Si, Sn, Ta, W, V, and Zn of 0.5 to 15 mol%. These elements, together with Fe and Pt, are components of the metal phase, and by containing 0.5 to 15 mol%, the magnetic properties of the sputtering target having Fe and Pt as basic components are further improved. The content of the element is more preferably 2 to 13 mol%, and even more preferably 4 to 11 mol%.
[0016] The sputtering target according to the embodiment of the present invention may selectively contain impurities, with the remainder being an oxide. When SiO2 is used as the oxide, a particularly preferable magnetic thin film can be obtained. In addition to SiO2, the oxide may further contain one or more oxides of elements selected from Al, B, Ba, Be, Ca, Ce, Cr, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr in order to further improve the magnetic properties.
[0017] In the sputtering target according to the embodiment of the present invention, the volume fraction of oxide is 40 vol.% or more. When the volume fraction of oxide in the sputtering target is 40 vol.% or more, the magnetic properties are further improved. There is no particular upper limit to the volume fraction of oxide in the sputtering target, but from the viewpoint that the magnetic properties deteriorate when there is too much oxide, it is preferably 60 vol.% or less. Moreover, the volume fraction of oxide in the sputtering target is more preferably 40 to 55 vol.%, and even more preferably 40 to 50 vol.%. The volume fraction of oxide can be calculated from the composition of the target, and the volume of each component contained in the target is calculated by (content of each material: mol) × (molecular weight of each material: g / mol) × (reciprocal of density of each material: cm 3Next, the volume fraction of oxides can be calculated by dividing the total volume of only oxides among the components by the total volume of all components.
[0018] Impurities selectively contained in the remainder of the sputtering target according to the embodiment of the present invention include metal elements not included in the elements (1) to (3) above, and simple substances or compounds of elements such as C or N from gas components such as carbon dioxide and nitrogen in the atmosphere. The content of the impurities selectively contained in the remainder of the sputtering target according to the embodiment of the present invention may be 0.5 mol% or less, or 0.15 mol% or less. In addition, the impurities can be analyzed by taking an analysis sample from the sputtering target and using infrared absorption spectrometry, an ICP emission spectrometer, GDMS (glow discharge mass spectrometry), or the like. The amount and shape of the analysis sample vary depending on the analysis method used, and the optimal amount and shape for each method can be selected.
[0019] The sputtering target according to the embodiment of the present invention has an average grain size of 4.0 μm2 of the oxide phase, calculated using a scanning electron microscope (SEM) image with a field magnification of 3000 times and ImageJ (image processing software). 2 The average grain area of the oxide phase of the sputtering target calculated using ImageJ is 4.0 μm 2If the oxide structure is finer and dispersed, the oxide phase and the phase containing Fe and Pt have a complicated structure, and even if a minute defect that can develop into a crack occurs, the boundary between the oxide phase and the phase containing Fe and Pt acts as a barrier to prevent the defect from developing, and it is presumed that the defect is prevented from becoming a crack or a break. Therefore, in the manufacturing process of the sputtering target, the occurrence of cracks or breaks can be effectively prevented in the hot pressing of the mixture obtained by crushing and mixing the powders of the raw materials, and in the subsequent HIP processing for increasing the density of the sintered body. The average grain area of the oxide phase of the sputtering target calculated using ImageJ was 3.0 μm 2 Preferably, it is 2.6 μm or less. 2 More preferably, it is 2.5 μm or less. 2 More preferably, it is 2.0 μm or less. 2 More preferably, it is 1.7 μm or less. 2 More preferably, it is 1.5 μm or less. 2 More preferably, it is 1.0 μm or less. 2 The lower limit of the average grain area of the oxide phase of the sputtering target calculated using ImageJ does not need to be particularly limited, but is, for example, 0.1 μm 2 It may be more than 0.2 μm, for example. 2 It may be 0.3 μm or more, for example. 2 It may be 0.4 μm or more, for example. 2 It may be more than 0.5 μm, for example. 2 It may be more than 0.6 μm, for example. 2 It may be more than that.
[0020] A method for measuring the average grain size of the oxide phase of a sputtering target according to an embodiment of the present invention will be described in detail. First, the sputtering target is cut and the cross section is mirror-polished to prepare an SEM observation sample. Next, the SEM observation sample is observed using, for example, an SEM (S-3700N, manufactured by Hitachi High-Technologies Corporation). The observation settings are as follows: Image captured: secondary electron image, field of view magnification: 3000x, accelerating voltage: 10-15kV The average grain area of the oxide phase can be evaluated by binarizing the secondary electron image obtained by the above-mentioned photographing using the image analysis software ImageJ according to the following steps (1) to (7). (1) Click File → Open on the ImageJ toolbar to load an SEM image with a magnification of 3000x. (2) Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. (3) Select the part of the image excluding the scale and cut out the scaled part by selecting Image → Crop. (4) Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. (5) Select Process → Binary → Make Binary. This completes the binarization of the image. (6)Select Analyze→Set measurement and check Area. (7) Select Analyze → Analyze Particle, set the analysis conditions to Size: 0-infinity Circularity: 0.00-1.00 Show: nothing, check Summarize, and select OK. This will display the results, from which you can read the Average Size value. As described above, ImageJ performs binarization on the imported SEM image to convert the black particle parts in the SEM image to black, and the black particles are regarded as oxide phase particles, and their average particle area is calculated. The threshold value for the binarization is automatically set from the color histogram in the image. Figure 1 shows an example of the binarized image and the original image.
[0021] The sputtering target according to the embodiment of the present invention preferably has a bending strength of 300 MPa or more. If the bending strength is 300 MPa or more, the occurrence of cracks or breakage during the manufacturing process can be more effectively suppressed. The sputtering target according to the embodiment of the present invention more preferably has a bending strength of 350 MPa or more.
[0022] The bending strength of the sputtering target according to the embodiment of the present invention can be measured as follows. First, the sputtering target is cut out to prepare seven test pieces. As a specific example of the cutting method, the sputtering target is machined to a thickness of 3 mm using a lathe, and then cut into a size of 4 mm x 35 mm using discharge wire machining. Since the surface is oxidized, the surface is polished with #120 abrasive paper to remove the oxide film and prepare the sample. Next, the three-point bending strength of the test piece is measured under the following measurement conditions, and the average value is regarded as the bending strength of the sputtering target. <Measurement conditions> A bench-top material testing machine (STB-1225S) manufactured by A&D Co., Ltd. can be used as the measuring device. The bending strength of the sputtering target according to the embodiment of the present invention can be measured with reference to JIS R 1601:2008 "Test method for bending strength of fine ceramics". Table 1 shows the measurement conditions for the bending strength of the sputtering target according to the embodiment of the present invention and the measurement conditions for bending strength described in JIS R 1601:2008. As shown in Table 1, the measurement conditions for the bending strength of the sputtering target according to the embodiment of the present invention are different from the measurement conditions for bending strength described in JIS R 1601:2008 only for "radius of curvature of support", "length of test piece", "parallelism", "edge of test piece", "roughness Ra of test piece", and "number of test pieces".
[0023] [Table 1]
[0024] <Sputtering target assembly> The sputtering target according to the embodiment of the present invention may be bonded to a backing plate as necessary to form a sputtering target assembly. The sputtering target assembly may be mounted on a sputtering device and used. As the brazing material, indium or indium tin may be used. The sputtering target according to the embodiment of the present invention may be mounted on a sputtering device as it is without using a backing plate. The material of the backing plate is not particularly limited, and examples thereof include Cu, Ti, Mo, and alloys containing at least one of these (e.g., Cu-Ni-Si alloys (e.g., C18000, etc.), CuZn alloys, and CuCr alloys). The material of the backing plate preferably has a high thermal conductivity, and from this viewpoint, Cu is suitable.
[0025] <Manufacturing method of sputtering target> Hereinafter, a method for producing a sputtering target according to an embodiment of the present invention will be described in detail. The sputtering target according to the embodiment of the present invention can be produced by a powder sintering method. First, powders of each metal element are prepared. Alternatively, alloy powders of these metals (e.g., Fe-Pt powder) may be used instead of the powders of each metal element. The purity of these raw materials is usually 2N (99% by mass) or more, preferably 3N (99.9% by mass) or more, and more preferably 4N (99.99% by mass) or more. If the purity is lower than 2N, the sintered body contains a large amount of impurities, which may cause problems such as the desired physical properties not being obtained (e.g., generation of particles due to arcing). These raw materials can be appropriately prepared based on the composition and purity of the desired sintered body.
[0026] Then, these metal powders are weighed to obtain the desired composition, and mixed using a mixing device while also being pulverized. Non-magnetic particles may be mixed with the metal powder at this stage. As a mixing device, a ball mill, a mortar, etc. may be used, but it is preferable to use a powerful mixing method such as a ball mill. In addition, considering the problem of oxidation during mixing, it is preferable to mix in an inert gas atmosphere or in a vacuum. In addition, the mixing time is set to 0.1 to 48 hours. By increasing the mixing time of the raw materials, the average particle area of the oxide phase can be reduced. On the other hand, by shortening the mixing time of the raw materials, the average particle area of the oxide phase can be increased. From this viewpoint, the average particle area of the oxide phase is controlled by adjusting the mixing time of the raw materials.
[0027] The mixed powder thus obtained is molded and sintered using a hot press device to produce a sintered body. The molding and sintering is not limited to hot pressing, and plasma discharge sintering and hot isostatic sintering can also be used. The sintering conditions are 650 to 1400°C and 0.5 to 12 hours. By increasing the sintering temperature and / or lengthening the sintering time, the average particle area of the oxide phase can be increased. On the other hand, by decreasing the sintering temperature and / or shortening the sintering time, the average particle area of the oxide phase can be decreased. From this perspective, the average particle area of the oxide phase is controlled by adjusting the sintering temperature and sintering time.
[0028] The sintered body is then removed from the hot press and subjected to HIP (Hot Isostatic Pressing). HIP is an effective means for improving the density of the sintered body. The holding temperature during HIP is 650-1100°C, the holding time is 0.5-12 hours, and the pressure is 100 MPa or more. The sintered body thus obtained is then machined into a desired shape on a lathe to produce a sputtering target.
[0029] <Film formation method using sputtering targets> Using the sputtering target according to the embodiment of the present invention, a thin film that mainly constitutes a magnetic recording medium can be formed. Specifically, a sputtering device is used to sputter the surface of the sputtering target with accelerated argon ions, particles (sputter particles) are released from the sputtering target, and the sputter particles are deposited on the surface of a substrate that is placed in a position opposite to the sputtering target in advance, thereby forming a thin film on the surface of the substrate. The sputtering conditions can be appropriately set according to the desired film thickness, composition, etc. EXAMPLES
[0030] The following examples of the present invention are provided for a better understanding of the present invention and its advantages, and are not intended to limit the invention.
[0031] <Example 1> The sputtering target according to Example 1 was manufactured by the following manufacturing method. As raw powders, Fe powder, Pt powder, Ag powder, and SiO2 powder were prepared and weighed so that the composition was (30-45)Fe-(30-45)Pt-(5-15)Ag-(5-25)SiO2 (mol%). The raw powders were prepared so that the total composition was 100 mol%. At this time, amorphous powder was used for the SiO2 powder. Next, the weighed Fe powder, Pt powder, Ag powder, and SiO2 powder were put into a 5L ball mill pot together with zirconia balls and mixed for 4 hours.
[0032] Next, the mixed powder taken out of the ball mill pot was filled into a carbon mold and hot pressed. The hot pressing conditions were a vacuum atmosphere, a heating rate of 300°C / hour, a holding temperature (sintering temperature) of 900°C, and a holding time (sintering time) of 2 hours, and the material was pressurized at 30 MPa from the start of heating to the end of holding. After the holding, the material was naturally cooled in the chamber. Then, the sintered body taken out of the hot pressing mold was subjected to HIP processing. The HIP processing conditions were a heating rate of 300°C / hour, a holding temperature of 850°C, and a holding time of 2 hours, and the gas pressure of Ar gas was gradually increased from the start of heating, and the material was pressurized at 150 MPa during holding. After the holding, the material was naturally cooled in the furnace. In this way, a sputtering target according to Example 1 was produced.
[0033] <Examples 2 to 8, Comparative Example 1> The sputtering targets according to Examples 2 to 8 and Comparative Example 1 were produced in the same manner as in Example 1. The mixing time of the raw material powders, the hot press temperature, and the HIP holding temperature were set under the conditions shown in Table 2.
[0034] Average particle area of oxide phase First, the sputtering target was cut and the cross section was mirror-polished to prepare a SEM observation sample. Next, the SEM observation sample was observed using an SEM (S-3700N, Hitachi High-Technologies Corporation). The observation settings were as follows: Image captured: secondary electron image, field of view magnification: 3000x, accelerating voltage: 10-15kV The average grain area of the oxide phase was evaluated by binarizing the secondary electron image obtained by the above-mentioned photographing using the image analysis software ImageJ according to the following steps (1) to (7). (1) Click File → Open on the ImageJ toolbar to load an SEM image with a magnification of 3000x. (2) Select 8-bit from Image→Type. Draw a straight line along the scale bar, and select Analyze→Set scale to set the scale size. (3) Select the part of the image excluding the scale and cut out the scaled part by selecting Image → Crop. (4) Select Process→Filters→Gaussian Blur, enter 2 for Sigma, and click OK. (5) Select Process → Binary → Make Binary. This completes the binarization of the image. A screenshot of the setting conditions is shown in Figure 2. (6)Select Analyze→Set measurement and check Area. (7) Select Analyze → Analyze Particle, set the analysis conditions to Size: 0-infinity Circularity: 0.00-1.00 Show: nothing, check Summarize, and select OK. This will display the results, from which you can read the Average Size value. As described above, after importing the SEM image with ImageJ, a binarization process was performed to convert the black particle parts in the SEM image to black, and the black particles were regarded as oxide phase particles, and their average particle area was calculated. The threshold value for the binarization process was automatically set from the color histogram in the image.
[0035] Oxide volume ratio The volume fraction of oxides was evaluated by calculating the volume of each component in the target as follows: (content of each material: mol) x (molecular weight of each material: g / mol) x (reciprocal of density of each material: cm 3 Next, the volume fraction of oxides was calculated by dividing the total volume of oxides by the total volume of all components.
[0036] Bending strength Seven test pieces were prepared by cutting out the sputtering target samples. The sputtering target was machined to a thickness of 3 mm using a lathe, and then cut into pieces of 4 mm x 35 mm using discharge wire machining. Since the surface was oxidized, the surface was polished with #120 abrasive paper to remove the oxide film, and the samples were prepared. Next, the three-point bending strength was measured under the following measurement conditions, and the average value was taken as the bending strength of the sputtering target. Note that the bending strength test was not carried out for Examples 3 to 8. <Measurement conditions> A benchtop material testing machine (STB-1225S) manufactured by A&D was used as the measuring device. The bending strength of the sputtering target according to this test example was measured with reference to JIS R 1601:2008 "Test method for bending strength of fine ceramics" and was carried out under the "measurement conditions of this embodiment" shown in Table 1 above. That is, as shown in Table 1 above, the measurement conditions for the bending strength of the sputtering target according to this test example differ from the measurement conditions for bending strength described in JIS R 1601:2008 only for "radius of curvature of support", "test piece length", "parallelism", "edge of test piece", "roughness Ra of test piece", and "number of test pieces".
[0037] ·Cracks The surface of each of the sputtering targets of the Examples and Comparative Examples was visually inspected to evaluate whether or not there was any cracking. Based on this evaluation, it was determined whether or not the occurrence of cracks or breakage during the manufacturing process was suppressed.
[0038] [Table 2]
[0039] <Consideration> According to Table 2, the sputtering targets according to Examples 1 to 8 each have (1) Fe, (2) Pt, (3) one or more elements selected from Ag, Au, B, Co, Cr, Cu, Ga, Ge, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Si, Sn, Ta, W, V, and Zn, and (4) the balance, in which the atomic ratio of (1) Fe to (2) Pt is 34 to 55 at%, the total concentration of (1) Fe and (2) Pt is 50 mol% or more, the content of the element (3) is 0.5 to 15 mol% in total, the balance of (4) is an oxide, the volume fraction of the oxide is 40 vol.% or more, and the average grain area (Average size) of the oxide phase calculated using ImageJ using an SEM image with a field magnification of 3000 times is 4.0 μm 2 Therefore, the bending strength was good, and the occurrence of cracks and breakage during the manufacturing process was suppressed. In contrast, in Comparative Example 1, the average particle area (Average size) of the oxide phase calculated using ImageJ using an SEM image with a field magnification of 3000 times was 4.0 μm 2 This resulted in poor bending strength, and cracks and breakage occurred during the manufacturing process.
Claims
1. (1) Fe; (2) Pt; (3) one or more elements selected from Ag, Au, B, Co, Cr, Cu, Ga, Ge, Mn, Mo, Nb, Ni, Pd, Re, Rh, Ru, Si, Sn, Ta, W, V, and Zn; and (4) the balance; The atomic ratio of the (1) Fe to the (2) Pt is 34 to 55 at %, The total concentration of the (1) Fe and the (2) Pt is 50 mol % or more, The content of the element (3) is 0.5 to 15 mol% in total, The remainder of the (4) is an oxide, which may selectively contain impurities, and the volume fraction of the oxide is 40 vol.% or more; The average grain area (average size) of the oxide phase calculated using ImageJ using a SEM image with a field magnification of 3000 times was 4.0 μm 2 The sputtering target is as follows:
2. 2. The sputtering target according to claim 1, having a bending strength of 300 MPa or more.
3. The sputtering target of claim 1 , wherein the oxide comprises an oxide of Si.
4. The sputtering target according to claim 3, wherein the oxide further contains one or more oxides of elements selected from Al, B, Ba, Be, Ca, Ce, Cr, Dy, Er, Eu, Ga, Gd, Ho, Li, Mg, Mn, Nb, Nd, Pr, Sc, Sm, Sr, Ta, Tb, Ti, V, Y, Zn, and Zr.
5. A sputtering target according to any one of claims 1 to 4, A backing plate bonded to the sputtering target; A sputtering target assembly comprising:
Citation Information
Patent Citations
Sputtering target-backing plate assembly body
WO2011102359A1
Fe-pt-type ferromagnetic material sputtering target
WO2012029498A1
Sputtering target for magnetic recording medium, and process for producing same
WO2013133163A1
Sputtering target for magnetic recording film, and raw carbon material for use in producing same
WO2014175392A1
Quantization system for picture signal
JP1985030271A